Початкова шкільна освіта на західноукраїнських землях у другій половині ХІХ − на початку ХХ ст. та пробудження національної свідомості українців - Макарчук, Олена; Makarchuk, Olena (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Проаналізовано загальний стан початкової шкільної освіти в Австро-Угорщині; освітня політика та освітні реформи австро-угорського уряду другої половини ХІХ – поч. ХХ ст. щодо запровадження початкової шкіль-ної освіти на східних теренах монархії, пошуки західноукраїнською інтелігенцією оптимальних шляхів розвит-ку початкової освіти. Початкову шкільну освіту українською мовою показано як один із напрямів пробудження національної свідомості українців.. The article studies the overall status of elementary education in the Austro-Hungarian educational policy and reformations of the Austro-Hungarian government at the second half of the nineteenth century and at the beginning of the twentieth century, regarding the introduction of elementary education in the eastern states of the monarchy, the search of intellectuals in the Western Ukraine for the best ways to develop elementary education in Ukrainian as one of the directions of the national consciousness awakening of Ukrainians.
The Issue of Elementary Education in Western Ukraine in the Second Half of the Nineteenth and at the Beginning of the Twentieth Century and the Awakening of the National Consciousness of Ukrainians
Keywords: початкова шкільна освіта; Західна Україна у складі Австро-Угорщини; політичні реформи другої пол. ХІХ − поч. ХХ ст. в Австро-Угорщині; національна свідомість західних українців; elementary schooling; Western Ukraine as a part of the Austro-Hungarian political reforms of the second half of the nineteenth - at the beginning of the twentieth centuries in the Austro-Hungarian Monarchy; the national consciousness of western Ukrainians